Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-020-57843-9
|View full text |Cite
|
Sign up to set email alerts
|

Potent inhibition of HIV replication in primary human cells by novel synthetic polyketides inspired by Aureothin

Abstract: overcoming the global health threat of HiV infection requires continuous pipelines of novel drug candidates. We identified the γ-pyrone polyketides Aureothin/neoaureothin as potent hits by anti-HiV screening of an extensive natural compound collection. total synthesis of a structurally diverse group of Aureothin-derivatives successfully identified a lead compound (#7) superior to Aureothin that combines strong anti-HIV activity (IC 90 <45 nM), photostability and improved cell safety. Compound #7 inhibited de n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Docking results revealed that all compounds accommodated well in the binding sites with binding energies ranging from -5.7 to -10.1 kcal/mol ( Figure 6 ). Most compounds demonstrated binding energies similar to the reference molecules, and in some compounds ( 8 , 9 , 11 , 16 ), the binding energies to the RT enzyme were even better than that of the reference molecule. Compounds 4 and 16 indicated high binding affinities for HIV PR and RT binding sites with ∆G values of -8.4 and -10.1 kcal/mol, respectively.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Docking results revealed that all compounds accommodated well in the binding sites with binding energies ranging from -5.7 to -10.1 kcal/mol ( Figure 6 ). Most compounds demonstrated binding energies similar to the reference molecules, and in some compounds ( 8 , 9 , 11 , 16 ), the binding energies to the RT enzyme were even better than that of the reference molecule. Compounds 4 and 16 indicated high binding affinities for HIV PR and RT binding sites with ∆G values of -8.4 and -10.1 kcal/mol, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Then, a methanolic solution of compound 15 (1.5 g, 6.5 mmol) was added, and the mixture was stirred for 48 hours at room temperature. The resulting precipitate was collected by filtration under vacuum, washed with water and dried to afford compound 16…”
Section: Preparation Of 2-cyano-n'-hydroxy-33-diphenylacrylimidamide ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The mode of action of this compound is different from all current clinical anti-HIV drugs. It shuts down de novo virus production by inhibiting HIV gene expression and effectively inhibits a spectrum of clinical isolates, including all HIV genotypes (HIV-type 1 and HIV-type 2) (Herrmann et al 2020 ).…”
Section: Antiviral Infectionsmentioning
confidence: 99%